Case Report: Papillary thyroid carcinoma in Goltz–Gorlin syndrome - Costanza, Flavia; Papi, Giampaolo; Corrado, Stefania; Pontecorvi, Alfredo (Frontiers in Endocrinology, 2023)
Goltz-Gorlin syndrome (GGS), also known as focal dermal hypoplasia, is a rare X-linked disorder caused by pathogenic variants in the PORCN gene and characterized by several abnormalities, including skin and limb defects, papillomas in multiple organs, ocular malformations, and mild facial dysmorphism. To date, only about 300 cases have been described in the literature. A 16-year-old female patient, born with multiple congenital dysmorphisms consistent with GGS and confirmed by genetic exam, was referred to our outpatient clinic for the work-up of a thyroid nodule. Thyroid ultrasound showed a bilateral nodular disease with a 17 mm large hypoechoic nodule in the right lobe. Cytological exam of fine needle aspiration biopsy was suspicious for malignancy. Thus, she underwent total thyroidectomy plus lymphadenectomy of the right central compartment. Histological exam disclosed a Papillary Thyroid Carcinoma (PTC) with lymph node micro metastases. Radioiodine (131-Iodine) 2 This is a provisional file, not the final typeset article therapy was performed. At 3-and 6-month follow-up the patient did not present either ultrasound or laboratory PTC recurrence. To our knowledge, we report the first case of PTC in a GGS patient. Since thyroid cancer is rare among children and adolescents, we hypothesize that the PORCN pathogenic variant could be responsible for tumor susceptibility. We also provide an overview of the clinical findings in GGS patients already reported and discuss the possible pathogenetic mechanism that may underlie this rare condition, including the role of PORCN in tumor susceptibility.